PROBLEM FORMATION OF PROFESSIONAL AND COMMUNICATIVE COMPETENCE IN DOMESTIC PHILOLOGIST THEORY AND PRACTICE - Білоус, Н. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article considers the problem of formation of professional and communicative competence which is acquired by philologists. Much attention is paid to the influence of the competency-based approach on the process of training qualified philologists and experts in the field of translation as well as on the development of their communication skills for effective operation in civil aviation